2020
DOI: 10.1007/s00223-020-00776-2
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent PTH Administration Increases Bone-Specific Blood Vessels and Surrounding Stromal Cells in Murine Long Bones

Abstract: To verify whether PTH acts on bone-specific blood vessels and on cells surrounding these blood vessels, 6-weeks-old male mice were subjected to vehicle (control group) or hPTH (20 µg/kg/day, PTH group) injections for 2 weeks.Femoral metaphyses were used for histochemical and immunohistochemical studies. In control metaphyses, endomucin-positive blood vessels were abundant, but SMA-reactive blood vessels were scarce. In the PTHadministered mice, the lumen of endomucin-positive blood vessels was markedly-enlar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…PTH has been well-established as an inducer of osteogenesis in the osteoporotic patient and has been used in the treatment of various bone fractures in both osteoporotic and non-osteoporotic patients. This study, as well as the work of others, demonstrates that PTH also plays a role in directing the vascular tree towards intact bone [ 40 ] and towards the site of a fracture [ 21 , 25 ]. The osteogenic process required to achieve bone formation has been shown to rely on active vascularization, which is modulated by PTH both directly [ 41 ] and indirectly [ 31 ].…”
Section: Discussionsupporting
confidence: 62%
“…PTH has been well-established as an inducer of osteogenesis in the osteoporotic patient and has been used in the treatment of various bone fractures in both osteoporotic and non-osteoporotic patients. This study, as well as the work of others, demonstrates that PTH also plays a role in directing the vascular tree towards intact bone [ 40 ] and towards the site of a fracture [ 21 , 25 ]. The osteogenic process required to achieve bone formation has been shown to rely on active vascularization, which is modulated by PTH both directly [ 41 ] and indirectly [ 31 ].…”
Section: Discussionsupporting
confidence: 62%
“…Since endomucin, a marker of vascular endothelial cells (Kusumbe et al 2014; Zhao, Hasegawa, et al 2021), was localized around the blood vessels of the PDL, most Gli1/Tomato + cells were thought to be distributed near blood vessels (Fig. 1F).…”
Section: Resultsmentioning
confidence: 99%
“…Using PTH-administered animal models, we have reported that PTH stimulates the proliferation of preosteoblastic cells (Luiz de Freitas et al, 2009) (Fig. 4), as well as differentiation of perivascular cells surrounding endomucin-positive blood vessels into osteoblastic progenitors (Zhao et al, 2021). Luiz de Freitas et al (2009) have previously reported that intermittent PTH administration did not facilitate osteoblastic bone formation in the absence of osteoclasts, indicating that the PTH-driven anabolic effect depends on cell coupling from osteoclasts.…”
Section: Minimodeling and Remodeling Induced By Teriparatidementioning
confidence: 99%